2020
DOI: 10.1002/adfm.202000544
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Human Natural and Induced Regulatory T‐Cells in IL‐2 and CCL1 Supplemented Alginate‐GelMA Hydrogel for 3D Bioprinting

Abstract: Regulatory T-cells (Tregs) are important modulators of the immune system through their intrinsic suppressive functions. Systemic adoptive transfer of ex vivo expanded Tregs has been extensively investigated for allogeneic transplantation. Due to the time-consuming and costly expansion protocols of Tregs, more targeted approaches could be beneficial. The encapsulation of human natural and induced Tregs for localized immunosuppression is described for the first time. Tregs encapsulated in alginate-gelatin methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…[45] Additionally, the overall viabilities of the invasive MDA-MB-231 cells were significantly higher (89-99%) than that of MCF-7 cells (78-93%), confirming a variable degree of radiation resistance between cell types. [46][47][48] Morphological adaptations of cells have been known to be dependent on matrix elasticity in both normal and disease mimicking microenvironments. [49][50][51] Here, cells embedded within the biomimetic ECMs of varying stiffness levels were found to be stably encapsulated and unaffected by the continuous replacements of the culture medium.…”
Section: (4 Of 10)mentioning
confidence: 99%
“…[45] Additionally, the overall viabilities of the invasive MDA-MB-231 cells were significantly higher (89-99%) than that of MCF-7 cells (78-93%), confirming a variable degree of radiation resistance between cell types. [46][47][48] Morphological adaptations of cells have been known to be dependent on matrix elasticity in both normal and disease mimicking microenvironments. [49][50][51] Here, cells embedded within the biomimetic ECMs of varying stiffness levels were found to be stably encapsulated and unaffected by the continuous replacements of the culture medium.…”
Section: (4 Of 10)mentioning
confidence: 99%
“…In addition to potentially changing the inflammation at the islet implantation site, experiments in which T regs are either co-cultured, co-aggregated, or co-infused with islets have shown that T regs appear to affect the islets themselves ( 59 62 ). In a preclinical study, co-culture of T regs with the pancreatic islets altered production of inflammatory chemokines such as CCL2, CCL5, CXCL9, and CXCL10, produced by the islets themselves, benefitting islet graft survival after implantation under the kidney subcapsule ( 60 ).…”
Section: Tregs For Promoting Islet Engraftmentmentioning
confidence: 99%
“…131 This approach should be explored in cardiac repair grafts when considering that Tregs have been shown to be safe in clinical trials and are currently supplemented during liver transplants to suppress immune rejection. 131 For more information on Tregs and their mechanism of suppression graft immune rejection, authors refer the reader to the review by Romano et al 133…”
Section: Hydrogels As Transplant Matricesmentioning
confidence: 99%
“…One of the main limitations of these approaches remains the immune rejection of the transplanted graft. Nevertheless, a recent exciting report of Kim et al describes how this may be overcome by encapsulating regulatory T‐cells (Tregs) cocultured with murine pancreatic islets in alginate‐gelatin methacryloyl hydrogels for the treatment of type I diabetes mellitus 131 . This approach should be explored in cardiac repair grafts when considering that Tregs have been shown to be safe in clinical trials and are currently supplemented during liver transplants to suppress immune rejection 131 .…”
Section: Soft Biomaterials For Sc Deliverymentioning
confidence: 99%
See 1 more Smart Citation